Lower limb amputation problems - Matteucci, Pablo; Borsani, Jorge; Lateulde de Masliah, Zulema; Mazza, Milton; Puppo, Héctor; Rosasco, Carlos (Cirugía del Uruguay, 1975)
In a conference, speakers of different specialties discuss problems of practical interest in the management of pa.tients with amputations of their lower limbs. Special stress is laid on those situations which will anable the patient to walk with a prosthesis in an early period.